UPAYA PEMERINTAH INDONESIA MENGENDALIKAN BERITA PALSU - Arwendria, Arwendria; Oktavia, Ariska (BACA: Jurnal Dokumentasi dan Informasi, 2019)
The aim of this study to gain an understanding of the government's efforts to organize and control fake news in the democratic era, especially ahead of the 2019 election. This research used the qualitative research methods, with a critical discourse analysis approach. Data was obtained from news texts published by online media during in 2018. Especially those containing fake news relating to general elections. Data collection used documentation techniques. The results showed that what was needed to control fake news were by making people healthy in cyberspace. The government must worked together with various organizations to disseminate and educate the public regarding content in cyberspace. In addition, the government have also set up a special institution which was tasked with overseeing the circulation of news on the internet and testing the truth.